Pengaruh Pendekatan Ethno-RME Terhadap Kemampuan Komunikasi Matematis Siswa Kelas Vii SMPN 2 Bangkinang Kota - Marliana, Puja; Zulfah, Zulfah; Zulhendri, Zulhendri (Delta: Jurnal Ilmiah Pendidikan Matematika, 2024)
This research was motivated by the low mathematical communication skills seen in the learning outcomes of class VII students at SMP Negeri 2 Bangkinang Kota. This research aims to find out whether the mathematical communication abilities of class VII students at SMP Negeri 2 Bangkinang Kota who apply the Ethno-RME Approach are better than the ability to understand mathematical concepts of students who apply conventional learning. This type of research is experimental research, with a Simple Random Sampling sampling technique. The population in this study were class VII students of SMP Negeri 2 Bangkinang Kota for the 2022/2023 academic year. The research subjects consisted of class VIIB, totaling 24 people and VIIC, totaling 24 people. The data analysis technique used is the T test and N gain test with the help of SPSS 26. Based on the N-Gain Score test for the experimental class with the Ethno-RME approach which is 63%, which is in the quite effective category, it can be concluded that the use of the Ethno-RME approach is sufficient effective for improving students' mathematical communication skills.